Analisis Yuridis Batas Pertanggungjawaban Pidana dalam Alternative Dispute Resolution (ADR) Pasca Pemberlakuan KUHP Baru - Anggara, Arya Bayu; Laia, Aturkian (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The enactment of Law Number 1 of 2023 on the New Criminal Code (KUHP) brings a paradigmatic shift by recognizing restorative justice. This normative legal research aims to analyze the position of Alternative Dispute Resolution (ADR) in criminal-dimensional disputes, formulate the boundaries of criminal liability, and examine its legal implications. The results show that the position of ADR in the criminal realm is legitimate but limited, only covering civil consequences of crimes, complaint offenses, minor offenses, or cases meeting restorative justice requirements. The boundaries of criminal liability cannot be completely eliminated through ADR because the principle of legality and the public nature of criminal law still require state intervention. Unrestricted use of ADR potentially triggers the commercialization of justice, impunity, and weakening of criminal law's preventive function. This study recommends detailed and integrated technical guidelines by law enforcement agencies to operationally implement these boundaries consistently